GAMBARAN OBESITAS DAN KADAR KOLESTEROL BERDASARKAN UMUR DAN JENIS KELAMIN PADA PASIEN YANG BEROBAT DI RUMAH SAKIT HAJI MEDAN - Amriani, Amriani; Kardhinata, E. Harso; Sartini, Sartini (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2015)
This reseach aims to determine the relationship between obesity and blood lipid levels in patients who seek treatment at Hospital Haji Medan. The research uses descriptive method that is a picture of the number of people to pull data directly from secondary data sources, namely the medical records of all patients treated at the Hospital Haji Medan. Parameters measured were patient age, sex and analyzing the increasing number of patients from 2012 to 2013. The results showed that the samples of patients who are obese biggest is 41-60 year age range that is equal to 44.15%, normal conditions alone amounted to 25. 98%. The second age range who are obese in this study were 61-80 years is 11.04% and normal as much as 8.44 percent, and the third at 21-40 years of age as much as 1.95 obesity and 8.44% for normal conditions , obesity among men and women obtained the highest percentage calculations for obesity is on the female is 46.75% while the male percentage of 13.64%. ObesityÂ patients have cholesterol levels > 200 for a total percentage of 48.05%, while patients with normal conditions of 9.09%. Based on the age of the highest number of obese in the age group 41-60 years, while based on gender, obese women more than men.